Manajemen Islami sebagai Upaya untuk Meningkatkan Mutu Layanan dan Kepuasan Pasien Rumah Sakit Umum Daerah - Adji, Iwan Setiawan; Alghozi, Muhammad Hilmi; Nabilah, Aisyah; Arifinnia, Salwa Ghaisani Syariifah; Hanief, Sekar Mayang Raisa; Rosyita, Fadhilla Jihan (FORIKES, 2025)
The implementation of Islamic management in healthcare facilities, particularly government-owned hospitals, is becoming increasingly relevant as the public demand for services that are not only professional but also align with religious values. The purpose of this study is to explore the implementation of Islamic management in regional public hospitals in Indonesia and assess its impact on service quality, patient satisfaction, and implementation challenges. This study is a systematic literature review based on the PRISMA 2020 guidelines and the Cochrane Handbook. A literature search was conducted in Google Scholar, PubMed, Scopus, and Garuda using the keywords